Provinzalrömische Arbeiten - Stupperich, Reinhard (Karl Bernhard Stark, 2020)
Auch zu Ladenburg und Osterburken
Keywords: Stark, Carl Bernhard -- 1824-1879; Geschichte 1800-1900; Neuzeit 1800-1900; Ladenburg; Osterburken